2017
DOI: 10.7150/jca.19594
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Translation Initiation Factor 3b is both a Promising Prognostic Biomarker and a Potential Therapeutic Target for Patients with Clear Cell Renal Cell Carcinoma

Abstract: Eukaryotic translation initiation factors (eIFs) constitute a new class of therapeutic cancer targets. EIF3b is the major scaffold protein of eIF3 (the largest core of eIFs). We sought to define the role played by and the mechanism of action of eIF3b in patients with clear cell renal cell carcinoma (ccRCC). We found that high-level eIF3b expression in tumors was not only associated with an aggressive tumor phenotype, but was also independently prognostic for patients with ccRCC. Knockdown of eIF3b impaired the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…EIF3 promotes mRNA binding to 40S subunits and prevents premature binding of large ribosomal subunits to regulate eukaryotic protein synthesis [3] . Emerging studies have demonstrated that eIF3 plays a role in tumorgenesis and tumor progression [11] . Zang et al reported that eIF3b was a potential prognostic indicator and therapeutic target for ccRCC [11] , that EIF3b knockdown inhibited the Akt signaling pathway, thus suppressing cell proliferation by triggering apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…EIF3 promotes mRNA binding to 40S subunits and prevents premature binding of large ribosomal subunits to regulate eukaryotic protein synthesis [3] . Emerging studies have demonstrated that eIF3 plays a role in tumorgenesis and tumor progression [11] . Zang et al reported that eIF3b was a potential prognostic indicator and therapeutic target for ccRCC [11] , that EIF3b knockdown inhibited the Akt signaling pathway, thus suppressing cell proliferation by triggering apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies have demonstrated that eIF3 plays a role in tumorgenesis and tumor progression [11] . Zang et al reported that eIF3b was a potential prognostic indicator and therapeutic target for ccRCC [11] , that EIF3b knockdown inhibited the Akt signaling pathway, thus suppressing cell proliferation by triggering apoptosis. In addition, EIF3b inhibition also impaired epithelial-tomesenchymal transition (EMT), thus suppressing migration and invasion in vitro and in vivo [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, high levels of eIF3b have been detected in several tumors, such as hepatocellular carcinoma (HCC) 46 , osteosarcoma 47 , clear cell renal cell carcinoma (ccRCC) 48 , bladder cancer 49 , prostate cancer 49 , esophageal squamous cell carcinoma (ESCC) 50 , glioblastoma 51 , colon cancer 52 , breast cancer 53 and gastric cancer 54 . In ccRCC, high expression of eIF3b is not only associated with an aggressive tumor phenotype, but also is an independent predictor of patient prognosis 48 . Overexpression of eIF3b in ESCC was found to be associated with lymph node metastasis, tumor depth, and advanced TNM stage, and ESCC patients with a high- level of eIF3b expression have a shorter overall survival and disease-free survival than those with lower eIF3b expression (Fig.…”
Section: Functions Of Eif3bmentioning
confidence: 99%
“…3 (VI)] comes from a study of the effects of knockdown of the gene family of eukaryotic translation initiation factors (EIF) by RNAi in MCF10A cells. EIF3b is a promising prognostic biomarker and a potential therapeutic target for patients with clear cell renal cell carcinoma[32], and EIF4GI is a target for cancer therapeutics[33].The top pathway inTable S2[Fig. 4 (I)] is the 'Pathway of regulation of IGF activity by IGFBP'.…”
mentioning
confidence: 99%